A Noninvasive Stroke Volume Monitoring for Early Detection of Minimal Blood Loss: A Pilot Study. Issue 2 (February 2021) - Epstein, Danny; Guinzburg, Ariel; Sharon, Saar; Kiso, Shai; Glick, Yuval; Marcusohn, Erez; Glass, Yehuda Daniel; Miller, Asaf; Minha, Sa'ar; Furer, Ariel
Abstract: Introduction: Alternation in traditional vital signs can only be observed during advanced stages of hypovolemia and shortly before the hemodynamic collapse. However, even minimal blood loss induces a decrease in the cardiac preload which translates to a decrease in stroke volume, but these indices are not readily monitored. We aimed to determine whether minor hemodynamic alternations induced by controlled and standardized hypovolemia can be detected by a whole-body bio-impedance technology. Methods: This was a non-randomized controlled trial that enrolled healthy blood donors. Vital signs, as well as shock index and stroke volume (SV), were recorded using noninvasive cardiac system, a noninvasive whole-body impedance-based hemodynamic analysis system, during phlebotomy. Results: Sixty subjects were included in the study group and 20 in the control group. Blood loss of 450 mL resulted in a significant decrease in systolic blood pressure (5 mm Hg; 95% CI 3, 6) and SV (5.07 mL; 95% CI 3.21, 6.92), and increase in shock index (0.03 bpm/mm Hg; 95% CI 0.01, 0.05). Clinically detectable changes (≥10%) in blood pressure and shock index were detectable in 15% and 5%, respectively. SV decreased by more than 10% in 40% of blood donors. No significant changes occurred in the control group. Conclusion: Continuous noninvasive monitoring of SV may be superior to conventional indices (e.g., heart rate, blood pressure, or shock index) for early identification of acute blood loss. As an operator-independent and point-of-care technology, the SV whole body bio-impedance measurement may assist in accurate monitoring of potentially bleeding patients and early identification of hemorrhage.